2020
DOI: 10.1016/j.genhosppsych.2020.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Psychological symptoms among frontline healthcare workers during COVID-19 outbreak in Wuhan

Abstract: provinces in China announced the public health emergency. Psychological distress in the general population has been reported in China during the COVID-19 quarantine [1]. The healthcare system in Wuhan was quickly overwhelmed as tens of thousands of people with flu-like symptoms swarmed the hospitals. Frontline healthcare workers (HCWs) in Wuhan have been under tremendous pressure and risk of contracting COVID-19 since the beginning of the quarantine. As of February 12, 2020, 21,569 HCWs from other cities in Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

52
495
15
45

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(607 citation statements)
references
References 5 publications
52
495
15
45
Order By: Relevance
“…The increased risk of infection and stressful environment might have contributed to higher mental health impacts among health workers in China than in Nepal [5,8,31]. Mental health outcomes among health workers affect their work performance and to address this, specialised mental health services are required [8,32,33]. The higher perceived risk and having to stay in quarantine during the epidemic might not just result in short term impacts but also lead to long term mental health consequences among health workers [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased risk of infection and stressful environment might have contributed to higher mental health impacts among health workers in China than in Nepal [5,8,31]. Mental health outcomes among health workers affect their work performance and to address this, specialised mental health services are required [8,32,33]. The higher perceived risk and having to stay in quarantine during the epidemic might not just result in short term impacts but also lead to long term mental health consequences among health workers [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Three out of four health workers reporting inadequate precautionary measures in the workplace in this study re ects the vulnerability of health workers in Nepal to COVID-19 infections. Studies done globally [33,[41][42][43] have pointed out the need to equip health workers with PPE as well as provide psychological support to increase resilience to adverse mental health outcomes. This nding should persuade the government of the urgency of arranging adequate precautionary measures for reducing mental health burden among health workers in Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…6 Despite the potential benefits of such measures, it is also being increasingly recognized that they might also have both negative short-and long-term consequences for mental health 7 that are in addition to those resulting from the disease itself. 8 For example, a recent review article has shown that quarantine may be associated with a number of negative psychological outcomes, such as anger and posttraumatic stress, with factors such as financial loss and the socioeconomic distress that can result from quarantine possibly underpinning the emergence of psychological disorders. 9 Several factors suggest that a focus on mental health might be especially important in relation to the ongoing COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the rst hypothesis of the study, participants who reported higher levels of fear of COVID-19 also reported higher levels of anxiety and depression and such ndings are compatible with the previous research. Several studies reported that fear and panic concerning COVID-19 elevates the risk to develop mental health issues including anxiety and depression (Du et al, 2020;Guo et al, 2020;Huang & Zhao, 2020;Lai et al, 2020;Liu et al, 2020;Lu et al, 2020). In terms of the ndings regarding the mindfulness, to the best of knowledge, this is the rst study to investigate the relationship between fear of COVID-19 and mindfulness.…”
Section: Discussionmentioning
confidence: 92%